Small rosarylike infarctions in the centrum ovale suggest hemodynamic failure. - Krapf, H; Widder, B; Skalej, M (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE Lesions in the centrum ovale may be classified as microangiopathic (lacunar) lesions and hemodynamic infarctions. To distinguish between them, a size of more than 2 cm has been postulated for hemodynamic infarctions. The reliability of this criterion was assessed with MR imaging.METHODS In 16 patients with unilateral or bilateral occlusion or high-grade stenosis of the internal carotid artery (ICA), CO2 testing revealed an ipsilateral hemodynamic failure. Each hemisphere in these patients was assessed separately for the presence and size of centrum ovale lesions.RESULTS Five of the 16 patients suffered from large cortical infarctions with a probable embolic pathogenesis. In the remaining 11 patients (22 hemispheres), a hemodynamic failure was found in 15 hemispheres, due to occlusion (13 hemispheres) or high-grade ICA stenosis (two hemispheres). MR imaging revealed centrum ovale infarctions with a size of more than 2 cm in three of the 15 hemispheres. In eight hemispheres, multiple small lesions (< 1.5 cm; three to 30 per hemisphere) could be found with a rosarylike or sickle-shaped distribution. In none of these eight cases did MR images show lacunar infarctions in the typical regions of the brain.CONCLUSION Our results favor the assumption that the MR finding of multiple small (< 1.5 cm) rosarylike lesions in the centrum ovale seems to be typical in patients with hemodynamic failure due to severe ICA disease.